2007
DOI: 10.1097/qai.0b013e318061b5d9
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Serum Hepatitis C Virus (HCV) RNA Level and Response at Week 4 Are the Best Predictors of Relapse After Treatment With Pegylated Interferon Plus Ribavirin in HIV/HCV-Coinfected Patients

Abstract: High baseline serum HCV RNA level and lack of undetectable viremia at week 4 are the most significant predictors of relapse in HCV/HIV-coinfected patients treated with peg-IFN plus weight-based RBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The main reason for this result was the percentage of relapses among patients with an ETR. A high proportion of relapses has been observed previously in patients infected by HCV genotype 3 [38], [43], [44]. This has been attributed either to insufficient doses of RBV or to a short duration of treatment (24 weeks) when a RVR had not been achieved [38].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The main reason for this result was the percentage of relapses among patients with an ETR. A high proportion of relapses has been observed previously in patients infected by HCV genotype 3 [38], [43], [44]. This has been attributed either to insufficient doses of RBV or to a short duration of treatment (24 weeks) when a RVR had not been achieved [38].…”
Section: Discussionmentioning
confidence: 94%
“…Effectively, a higher relapse rate after completing a course of therapy could contribute to a lower SVR in this population [38]. Relapses were detected in 24 patients (13% of the total population, 21% of those with ETR), within the range seen in other series of coinfected patients treated with Peg-IFN plus RBV (range: 15%–37% of those with ETR) [38], [39]. Relapses were especially present in those individuals without a RVR (only one patient with RVR experienced relapse after suppression of anti-HCV therapy).…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of treatment response with peginterferon/ribavirin therapy are factors largely related to HCV: rapid virologic response (RVR), HCV genotype, HCV viral load, IL28B gene variation, and liver disease stage, however, the SVR rates in HIV/HCV co-infected patients are 15–20 % lower than those in patients with HCV mono-infection. Likewise, rates of hepatic decompensation during peginterferon/ribavirin treatment are considerably higher in co-infected patients than in HCV mono-infected patients, especially among cirrhotics [2, 128133]. For interferon-based treatment regimens, please refer to the previous report for further verification [1].…”
Section: Svr For Renal Failure and Co-infection With Hbv/hivmentioning
confidence: 99%
“…Two large registration trials have shown lower sustained virologic response rates (SVR) for dual therapy in HIV/HCV co-infected patients (~33%) compared to mono-infected patients (47-54%) [8-12]. Higher baseline HCV RNA levels and lower initial ribavirin doses are quoted as possible explanation for the lower SVR seen in co-infected patients [13]. Recent data suggest that higher ribavirin doses are safe and well-tolerated in co-infected patients [14].…”
Section: Introductionmentioning
confidence: 99%